Adsorption of oriented carborane dipoles on a silver surface. Issue 3 (10th December 2015) - Vetushka, Aliaksei; Bernard, Laetitia; Guseva, Olga; Bastl, Zdeněk; Plocek, Jiří; Tomandl, Ivo; Fejfar, Antonín; Baše, Tomáš; Schmutz, Patrik
Abstract : Modification of surfaces with self‐assembled mono‐layers (SAMs) represents a powerful and innovative tool for adjusting physical and chemical properties of surfaces. The adsorption of isomeric molecules with relatively strong and oppositely oriented molecular dipoles, 1, 2‐(HS)2 ‐1, 2‐C2 B10 H10 and 9, 12‐(HS)2 ‐1, 2‐C2 B10 H10, on a flat silver surface is investigated in order to adjust its work function in a desired way. Time‐of‐flight secondary ion mass spectroscopy (ToF‐SIMS) and X‐ray photoelectron spectroscopy (XPS) are used to prove that both isomers (i) chemisorb on a silver surface as thiolates and (ii) exhibit comparable surface densities. Densely packed surfaces of both SAMs are additionally investigated by electrochemical impedance spectroscopy, and effective surface passivation is observed. Co‐deposition of both derivatives is shown to enable effective and fine adjustment of the surface work function value within a range of ∼1 V, which is confirmed by Kelvin probe force microscopy (KPFM). Experimental data indicate faster SAM formation for the former isomer. Contribution of the interface Ag–S bonds to the work function changes is quantified.